2018
DOI: 10.1111/ajt.14623
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of everolimus with reduced tacrolimus in living-donor liver transplant recipients: 12-month results of a randomized multicenter study

Abstract: In a multicenter, open-label, study, 284 living-donor liver transplant patients were randomized at 30 ± 5 days posttransplant to start everolimus+reduced tacrolimus (EVR+rTAC) or continue standard tacrolimus (TAC Control). EVR+rTAC was non-inferior to TAC Control for the primary efficacy endpoint of treated BPAR, graft loss or death at 12 months posttransplant: difference -0.7% (90% CI -5.2%, 3.7%); P < .001 for non-inferiority. Treated BPAR occurred in 2.2% and 3.6% of patients, respectively. The key secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 36 publications
1
72
0
5
Order By: Relevance
“…Everolimus (EVE), a macrocyclic lactone derivative of Sirolimus, has recently emerged as a key maintenance immunosuppressive molecule in therapies for preventing acute and chronic allograft organ rejection [1,2,3]. EVE is successfully used in combination with cyclosporine and corticosteroids both in adult and paediatric population of renal- and cardiac-transplant recipients, but far less often for lung-transplant recipients [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Everolimus (EVE), a macrocyclic lactone derivative of Sirolimus, has recently emerged as a key maintenance immunosuppressive molecule in therapies for preventing acute and chronic allograft organ rejection [1,2,3]. EVE is successfully used in combination with cyclosporine and corticosteroids both in adult and paediatric population of renal- and cardiac-transplant recipients, but far less often for lung-transplant recipients [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Manzia et al began the study at postoperative day 1, Cillo et al began at postoperative day 7, while Masetti et al began the study at postoperative day 10. The randomization was performed for the rest of the included studies about 30 days after the surgery . Only one study followed the participants for <1 year.…”
Section: Resultsmentioning
confidence: 99%
“…The process of study inclusion is illustrated in Figure 1. A total of eight trials reported in 12 articles [7][8][9]13,14,[20][21][22][23][24][25][26] were included in the present study. De Simone et al 21 recruited the maintenance liver transplant recipients.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations